New Exclusion for Children with Special Needs Case Study in Inclusive School in Banyumas Regency - Desta Riani, Aan; Suyanto, Edy; Retno Wulan, Tyas (Yinyang: Jurnal Studi Islam Gender dan Anak, 2025)
Inclusive education implemented in Banyumas Regency has attempted to provide opportunities for children with special needs to get education together with other students. The practice of inclusive education still experiences many challenges in its implementation and can even create new exclusions for children with special needs in various forms. This study aims to identify new forms of exclusion for children with special needs in inclusive schools in Banyumas Regency. The research method uses a qualitative method with a case study approach, research informants were determined using purposive sampling consisting of class teachers, special assistant teachers, students with special needs, principals and parents of students with special needs. and analyzed using interactive analysis. The study results found that new forms of exclusion for children with special needs were based on failures in recognition based on Axel Honneth's recognition theory, the purpose of recognition is to build a just and social relations that are fair and equal social relations in society. Honneth's form of recognition of love, law and solidarity. According to him, a lack of recognition can trigger feelings of injustice which can lead to conflict Forms of exclusion include exclusion in the form of love, legal or structural exclusion, and cultural solidarity exclusion. Inclusive education organizers need to evaluate the inclusive education program to provide full services.